Outcomes and Benefits of a Managerial Global Mind‐set: An Exploratory Study with Senior Executives in North America and India. (March 2014) - Ananthram, Subramaniam; Nankervis, Alan R.
<x xml:space="preserve">Abstract</x> Globalization and its associated challenges are compelling managers in multinational corporations to develop appropriate skill sets. An emerging body of research in international management has suggested that meeting this challenge requires the cultivation and development of a managerial global mind‐set. There has been limited empirical work on the outcomes and benefits of a managerial global mind‐set and consequently this article attempts to fill that gap. Based on semistructured interviews with a total of 56 senior executives of multinational corporations in North America (United States and Canada) and India, this study identifies five outcomes of a global mind‐set with benefits for managers and their organizations. The findings have theoretical implications, which are discussed along with their practical applications for multinational corporations, their senior executives, and human resource professionals, with respect to identifying management development programs that assist in the cultivation and nurturing of a global mind‐set. © 2014 Wiley Periodicals, Inc.